Condition monitoring of structures under non-ideal excitation using low cost equipment - Paupitz Gonçalves, Paulo J. [UNESP]; Silveira, Marcos [UNESP] (My University, 2017)
Monitoring the integrity of structures and machines is an evergrowing concern in engineering applications. Better knowledge of structural conditions allows optimized maintenance cycles, increasing the availability and return of investment, and preventing failure of various systems from manufacturing equipment to air and land vehicles. A common way of evaluating the integrity of mechanical systems is capturing and analyzing vibration signals during operation. Many of the condition monitoring systems are highly specialized, incurring high initial investment. In this context, the objective of this work is to demonstrate the possibility of using low-cost systems for monitoring the integrity of structures. The use of piezoelectric sensors to capture vibration signals is currently ubiquitous, and acquisition and conditioning of these signals can be performed by low cost and open source logic programmable microcontrollers such as Arduino. Structures coupled to non-ideal motors (such that the phenomenon of resonance capture can occur) are used in this study. Controlled structural modifications are performed by the addition of point masses along the length of the beam, and by the application of magnetomotive forces with the use of an electromagnet at a fixed point on the beam. The experimental data is compared to analytical and numerical results, and to an established commercial system, demonstrating the possibility of satisfactory monitoring of structural integrity with such system.
Keywords: Condition monitoring; Low cost; Non-ideal excitation; Sommerfeld effect